HUBUNGAN BELANJA MODAL DENGAN BELANJA PEMELIHARAAN PADA PEMERINTAH KABUPATEN/KOTA (Studi Kasus Di Wilayah Sumatera Bagian Selatan) - -, Baihaqi; Khotimah, Husnul (Jurnal Manajemen dan Keuangan, 2009)
This research aims to give an empirical evidence about the connection between capital expenditure and maintenance expenditure in Sumbagsel Government of Regency/Municipality, and whether in regency areas are higher than municipality in Sumbagsel areas. The source of data analysis come from APBD Realization report of regency & municipality in Sumbagsel area.The analysis found that, overall, capital expenditures of 2005 and 2006 had a significance correlation with maintenance expenditure, in regency and municipality Government. Only one test didnât show correlation that is between capital expenditure 2005 and maintenance expenditure 2006 in regency area which is amounting to 0.037.The correlation of capital expenditure & maintenance expenditure between regency/municipality government in Sumbagsel area was not different significantly in 2005 and 2006 which is proved by R2 < t-table = 1,746. This invention means, there is a group of regency/municipality area which is rich and poor in Indonesia and this condition was caused by a different potention of nature resources in that regency/municipality.Keyword: capital expenditure, maintenance expenditure.